Optical coherence tomography angiography in wet age-related macular degeneration (AMD) - MarquesJoão Pedro; SilvaRufino (眼科学报; 卷 31, 编号 1 (March 2016): 《眼科学报》, 2016)
Over the last decades, substantial developments in retinal imaging offered a paradigmatic change in the understanding of the pathophysiology of wet age-related macular degeneration (AMD). We have reached a point of sophistication that seemed unattainable a few years ago. A myriad of imaging devices is now available at our discretion, representing a unique opportunity to offer our patients better clinical care. In order to reduce the risk of progressive and enduring visual loss associated with wet AMD, early identification and prompt initiation of treatment is warranted. Since its introduction in 1961 by Novotny and Alvis (1), fluorescein angiography (FA) became the gold standard for the diagnosis and classification of choroidal neovascularization (CNV). However, a major limitation of traditional angiography resides in its inability to image the entire retinal capillary system or to directly visualize new vessels, resorting on indirect clues such as fluid accumulation or leakage to recognize neovascularization (2). Wide-field image acquisition, confocal scanning laser ophthalmoscopy, adaptive optics and indocyanine green angiography (ICGA) have broadened the use of classic angiography. With complementary ICGA, better visualization of the deep vessels can be obtained due to peak excitation (805 nm) and emission (835 nm) in the near-infrared region. Nevertheless, ICGA is neither available nor routinely performed in many institutions throughout the world. Also, despite the ability to detect dynamic patterns of dye transit and leakage, angiography systems (FA and ICGA) remain expensive, time-consuming and invasive procedures. Although generally safe, side effects like nausea; vomiting or even severe allergic reactions may develop in a minority of patients, thus limiting its repeated use (3).